Treatment of Poxvirus Infections in Rabbits with 9-β-d-Arabinofuranosyladenine - Klein, Richard J. (1974)
The antiviral efficacy of 9-β-d-arabinofuranosyladenine (ara-A) was evaluated in localized lesions produced by the intradermal inoculation of rabbits with vaccinia virus (VV) and rabbit Shope fibroma virus (SFV). Ara-A administered intraperitoneally suppressed or significantly reduced the cutaneous pustular lesions produced by VV as well as the benign skin tumors caused by the SFV. With a daily dose of 300 mg/kg given for 5 days starting at the time of infection, or with 600 mg/kg daily starting 3 days after inoculation, we were able to suppress completely the formation of tumors induced by the SFV. The appearance of pustular lesions induced by VV was completely suppressed by a dose of 600 mg of ara-A per kg given for 3 days when the treatment was initiated at the time of infection, but a significant reduction in the number of pustular lesions was obtained with a single dose of 600 mg/kg, or with five doses of 300 mg/kg starting 24 h after inoculation. No toxic effect of ara-A was noted in the treated rabbits.